Hydrotalcite monolayer toward high performance synergistic dual-modal imaging and cancer therapy. (May 2018) - Mei, Xuan; Wang, Wei; Yan, Liang; Hu, Tingting; Liang, Ruizheng; Yan, Dan; Wei, Min; Evans, David G.; Duan, Xue
Abstract: Recently, theranostic has drawn tremendous attention by virtue of the nanotechnology development and new material exploration. Herein, we reported a novel theranostic system by loading Au nanoclusters (AuNCs) and Chlorin e6 (photosensitizer, Ce6) onto the monolayer nanosheet surface of Gd-doped layered double hydroxide (Gd-LDH). The as-prepared Ce6&AuNCs/Gd-LDH exhibits a largely enhanced fluorescence quantum yield (QY) of 18.5% relative to pristine AuNCs (QY = 3.1%) as well as superior T1 magnetic resonance imaging (MRI) performance ( r 1 = 17.57 mM −1 s −1 ) compared with commercial MRI contrast agent (Gd(III)-1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid (Gd-DOTA): r 1 ≈ 3.4 mM −1 s −1 ), resulting from a synergistic effect between AuNCs and Gd-LDH. In addition, both in vitro and in vivo therapeutic evaluations demonstrate an efficient dual-modality imaging guided anticancer performance, especially the synergetic enhanced magnetic resonance/fluorescence (MR/FL) visualization of tumor site. Therefore, this work demonstrates a successful paradigm for the design and preparation of LDHs monolayer-based theranostic material, which holds great promises in practical applications.